The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41598-021-82850-9
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization and mortality associated with SARS-CoV-2 viral clades in COVID-19

Abstract: The COVID-19 epidemic of 2019–20 is due to the novel coronavirus SARS-CoV-2. Following first case description in December, 2019 this virus has infected over 10 million individuals and resulted in at least 500,000 deaths world-wide. The virus is undergoing rapid mutation, with two major clades of sequence variants emerging. This study sought to determine whether SARS-CoV-2 sequence variants are associated with differing outcomes among COVID-19 patients in a single medical system. Whole genome SARS-CoV-2 RNA seq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 35 publications
4
49
0
Order By: Relevance
“…They showed that 17 variants had a two-fold higher risk of severe COVID-19, while 67 variants were associated with less severe COVID-19 [33]. This is in line with another study from France and the US, suggesting that different viral variants may result in different infection severity and risk of hospitalization [34,35]. Since SARS-CoV-2 is an RNA virus, its dynamic evolution is expected to in uence its biological characteristic [36], including its virulence and pathogenicity [33].…”
Section: Discussionsupporting
confidence: 68%
“…They showed that 17 variants had a two-fold higher risk of severe COVID-19, while 67 variants were associated with less severe COVID-19 [33]. This is in line with another study from France and the US, suggesting that different viral variants may result in different infection severity and risk of hospitalization [34,35]. Since SARS-CoV-2 is an RNA virus, its dynamic evolution is expected to in uence its biological characteristic [36], including its virulence and pathogenicity [33].…”
Section: Discussionsupporting
confidence: 68%
“…A study conducted on isolates from patients in Washington, US, allowed the identification of two major clades distinguished by twelve polymorphisms in five genes. No significant difference regarding mortality was observed among patients infected with these two clades [43]. In a study conducted on 88 patients in the USA, most of the sequences (93%) were clustered in three main clades (clades 1, 2 and 3), defining mutations at the US level.…”
Section: Relation Between Viral Mutations and Severity Of Covid-19 Infectionmentioning
confidence: 94%
“…Of the 63 publications included, five were non-peer reviewed preprints [16,17,52,54,66]. Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73]. The remaining 33 articles analyzed SARS-CoV-2 genomes downloaded from the GISAID or other available databases with patient status [8][9][10][11]20,21,[30][31][32][33][34][35][36]40,50,…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early detection and prognosis studies that integrated heterogenous data ( Table 3 ), 8 studies imputed missing data. Most studies performed simple imputation based on mean, mode, or median values, while 2 studies performed multivariate imputation by chained equations, 100 , 104 and 1 study imputed missing values using bagging trees. 96 …”
Section: Resultsmentioning
confidence: 99%